E-Wallet System with Fingerprint Authentication (Evolet) - Sen, Wong Jin; Lukose, Jacqueline; May, Chong Mien (Journal of Applied Technology and Innovation, 2020)
Evolet aims to improve convenience by replacing all physical cash into the virtual payment method which can be performed by our smartphone. In response to replacing cash with phone, payment can actually be done much safer in the sense that miscounted payment amount will be reduced. Since most of the people nowadays carry their own smartphone to different places, they can actually keep their wallet at home while still able to make transaction at stores and restaurant. Not forgetting the indirect benefits by minimizing loses from robbery due to the virtual money being brought along with them. In short, this virtual payment system improve convenience by letting users to make payments via smartphone.